Finding food in the hunger season: A mixed methods approach to understanding wild plant foods in relation to food security and dietary diversity in southeastern Madagascar - Moore, Maya; Alpaugh, Mattie; Razafindrina, Kimmerling; Trubek, Amy B.; Niles, Meredith T. (Frontiers in Sustainable Food Systems, 2022)
In many rural farming societies, wild plant foods (WPFs) continue to play an important role in everyday diets as well as in coping with hunger during food shortages. However, WPF collection and consumption may pose challenges to biodiversity conservation efforts (e.g., in protected areas), and some “famine foods,” foods not typically eaten under normal conditions, may have deleterious health impacts. Using data from a cross-sectional survey of 328 smallholder farmers and fisherfolk living in 15 villages surrounding Manombo Special Reserve on the southeastern coast of Madagascar, we examine the relationship between food security, dietary diversity, and consumption of WPFs, specifically giant aquatic arrowhead or via (Typhonodorum lindleyanum) and Polynesian arrowroot or tavolo (Tacca leontopetaloides), during the region's main lean season. We complement survey findings with focus group interviews to document traditional ecological knowledge and perceptions of these WPFs, including how tavolo and via are rendered edible, as well as human health effects from collecting, preparing, and eating them. Using multilevel logistic regression modeling, we found that consumption of these WPFs were significantly associated with inadequate nutrition among farmers. Wealthier households were less likely to consume these WPFs as a coping strategy during food insecure periods, while larger and more food insecure households were more likely to consume them. These findings reaffirm the importance of access to natural areas and support the design of protected area conservation strategies that honor local foodways and consider WPFs that serve as food safety nets for more vulnerable populations.